DRIVERS OF DEGRADATION OF PASTURES IN THE CERRADO NORTH OF MINAS GERAIS - BR - Pereira da Silva, Lucas Augusto; Sena-Souza, João Paulo; Pereira de Souza, Cristiano; Silva, Claudionor Ribeiro; Bolfe, Edson Luis; Chagas-Reis, Carolina Cabral; Leite, Marcos Esdras (Ra’e Ga: o Espaço Geográfico em Análise, 2023)
The Brazilian Cerrado Biome is a strategic region for livestock, with a high concentration of pastures and cattle. Approximately 30% of these pastures have some degree of degradation, especially in semi-arid regions. The northern region of the state of Minas Gerais portrays this context well. Therefore, identifying the degradation vectors is a fundamental step in agro-environmental planning. This study aims to develop a model to evaluate the vectors of degradation of pastures in Cerrado north of Minas Gerais. The methodological structure was based on i) mapping of the pasture degradation index (PDI) using remote sensing techniques, ii) setting up a database with predictive variables representing socioeconomic, relief and climatic aspects, and iii) elaboration of a model to evaluate the vectors of pasture degradation with multiple linear regression. The PDI mapping showed that the pastures in all municipalities present some degree of degradation. Eighteen municipalities (21%) have moderately degraded pastures and 66 municipalities (79%) predominantly have pastures with mild degradation levels. According to the statistical model, the degradation of pastures is explained by climatic vectors, specifically by air temperature, seasonality of precipitation and annual precipitation (R² = 0.50, p-value < 0.001). The management of pastures in the region must consider these environmental factors, aiming at a more sustainable livestock in the Cerrado of northern Minas Gerais.